2007
DOI: 10.1134/s0006297907130044
|View full text |Cite
|
Sign up to set email alerts
|

Photoactive pigment—enzyme complexes of chlorophyll precursor in plant leaves

Abstract: This review summarizes contemporary data on structure and function of photoactive pigment--enzyme complexes of the chlorophyll precursor that undergoes photochemical transformation to chlorophyllide. The properties and functions of the complex and its principal components are considered including the pigment (protochlorophyllide), the hydrogen donor (NADPH), and the photoenzyme protochlorophyllide oxidoreductase (POR) that catalyzes the photochemical production of chlorophyllide. Chemical variants of the chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 164 publications
0
24
0
Order By: Relevance
“…However, in the present review, we focus on another enzyme, POR, which requires light for both catalysis and to induce a conformational change, which switches the enzyme from an inactive into a fully active state. A detailed review on POR, including studies on the POR A and B isoforms from green plants, can be found in [21][22][23]. In the present study, we provide a limited overview of previous spectroscopic investigations of the isolated POR complex from cyanobacteria, with a particular focus on recent time-resolved transient absorption experiments.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the present review, we focus on another enzyme, POR, which requires light for both catalysis and to induce a conformational change, which switches the enzyme from an inactive into a fully active state. A detailed review on POR, including studies on the POR A and B isoforms from green plants, can be found in [21][22][23]. In the present study, we provide a limited overview of previous spectroscopic investigations of the isolated POR complex from cyanobacteria, with a particular focus on recent time-resolved transient absorption experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the last decade a series of such studies have been reported. [22] In a similar manner, the enzymes obtained from the extraction of etiolated plant material, PChlide holochromes, form high molecular weight complexes (~600 kDa), too. [1][2][3][4][5][6][7] In addition, the thermodynamics of substrate/coenzyme binding as well as the complete POR catalytic cycle have been investigated by spectroscopic techniques in conjunction with low-temperature and stopped flow methods.…”
mentioning
confidence: 97%
“…They all include recombinant POR enzymes, which were expressed in Escherichia coli and reconstituted to the ternary enzyme complexes by addition of the substrate and coenzyme, protochlorophyllide (PChlide) and NADPH, respectively. [22] In a similar manner, the enzymes obtained from the extraction of etiolated plant material, PChlide holochromes, form high molecular weight complexes (~600 kDa), too. All these experiments were also performed on recombinant enzymes expressed in Escherichia coli or on a pigment-free, monomeric enzyme isolated from etiolated oat (Avena sativa) seedlings.…”
mentioning
confidence: 97%
See 2 more Smart Citations